Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1103/physrevresearch.2.033027
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic resetting on comblike structures

Abstract: We study a diffusion process on a three-dimensional comb under stochastic resetting. We consider three different types of resetting: global resetting from any point in the comb to the initial position, resetting from a finger to the corresponding backbone and resetting from secondary fingers to the main fingers. The transient dynamics along the backbone in all three cases is different due to the different resetting mechanisms, finding a wide range of dynamics for the mean squared displacement. For the particul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 56 publications
1
49
0
Order By: Relevance
“…To analyze the diffusion dynamics numerically, we use a system of Langevin equations in the presence of drift and stochastic resetting to the initial position [33,44]:…”
Section: Langevin Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…To analyze the diffusion dynamics numerically, we use a system of Langevin equations in the presence of drift and stochastic resetting to the initial position [33,44]:…”
Section: Langevin Equationmentioning
confidence: 99%
“…It was shown that the solution for the PDF approaches a non-equilibrium steady state and, in the long-time limit, its MSD is saturated, x 2 (t) ∼ 1/r (also see the review paper [31] for more details). Moreover, Brownian motion in a two-dimensional comb in the presence of stochastic (Markovian) resetting can be solved analytically [32][33][34]. The marginal PDFs along both the backbone and fingers approach non-equilibrium steady states, and the MSDs are saturated according to the resetting rate: x 2 (t) ∼ 1/ √ r and y 2 (t) ∼ 1/r [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resetting can produce a counterintuitive effect: it renders an infinite mean first passage time (MFPT) finite, which can be also minimized at a specific resetting rate. Some extensions have been made in the field, such as temporally or spatially dependent resetting rate [13][14][15], higher dimensions [16,17], complex geometries [18][19][20], noninstantaneous resetting [21][22][23][24], in the presence of external potential [25][26][27], or in the presence of multiple targets [28][29][30], other types of Brownian motion, like runto-tumble particles [31][32][33], active particles [34,35], and so on [36]. These nontrivial findings have triggered enormous recent activities in the field, including statistical physics [37][38][39][40][41][42], stochastic thermodynamics [43][44][45], and single-particle experiments [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, a prevalent real world observation conforms that selfreproduction is characterized with a stationary distribution that has power law tails, which hinders the practical implementation of the model [8]. A natural way to invoke stationarity is to adapt GBM with a stochastic resetting mechanism which has recently spurred extensive research interests in statistical physics [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], stochastic processes [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and in single particle experiments [42,43].…”
mentioning
confidence: 99%